Prevalence and determinants of overweight/obesity among under-five children in sub-Saharan Africa: a multilevel analysis - Belete Achamyelew Ayele; Sofonyas Abebaw Tiruneh; Asnakew Achaw Ayele; Melkamu Aderajew Zemene; Ermias Sisay Chanie; Habtamu Shimels Hailemeskel (BMC, 2022)
Abstract Introduction Childhood obesity has become a major public health problem for both developed and developing nations. It is uncommon to find under-nutrition in many low and middle-income countries; as well, obesity is a double burden in these settings. This study aimed to investigate the pooled prevalence of overweight /obesity among under-five (under-5) children in sub-Saharan Africa (SSA). Methods Data were accessed from the recent nationally representative demographic and health survey datasets from 33 SSA Countries. A total of 192,132 under-five children were recruited for this study. The pooled prevalence of overweight /obesity among under-5 was done using random-effects meta-analysis command. Multivariable multi-level mixed-effects logistic regression analysis was used to identify determinants for the prevalence of under-5 overweight and/or obesity. A P-value less than 0.05 was used to declare statistical significance. Results The pooled prevalence of overweight /obesity among under-5 was 5.10% (9% CI: 4.45 - 5.76) in SSA. South Africa region (8.80%, 95% CI: 4.18 - 13.42) had a higher prevalence of under-5 overweight and/or obesity followed by the East Africa region. Male under-5 children (adjusted odds ratio (AOR) = 1.09, 95 confidence interval (CI): 1.02 - 1.25), Larger birth weight under-5 children (AOR = 1.39, 95% CI: 1.26 - 1.54), under-5 children aged older two to three years (AOR = 0.85, 95% CI: 0.76 - 0.94), under-5 children born from educated mothers (secondary and above) (AOR = 1.12, 95% CI: 1.01 - 1.25), and under-5 children living in the West Africa (AOR = 0.67, 95% CI: 0.56 - 0.81) and South Africa (AOR = 1.87, 95% CI: 1.09 - 3.21) were significant determinants for under-5 overweight and/or obesity. Conclusion Childhood obesity is becoming a great challenge and double burden in developing nations. In SSA Africa 1 in 20 under 5 children were overweight and/or obese. Male under-5 children, older aged, under-5 children born from educated mothers, and under-5 children living in the South Africa region were at higher risk for developing overweight and/or obesity. Thus, SSA countries should implement early to pause these consequences preventing the double burden of undernutrition.